Getting forestry research into policy and practice - Spilsbury, M.J. (2002)
The paper applies a broad-brush perspective to policy change processes, forestry research and innovation. It considers patterns of research and impact and the impacts linked to them in developing countries. It highlights some research successes, failures opportunities and constraints in the hope of improving the focus and relevance of future efforts. It highlights the fact that for most of last century, forestry research was predominantly focused on achieving 'efficiency gains' in forest production systems, and that this focus was shared by both private enterprise and prevailing approaches to broader 'development' in developing countries. It asserts that there has been difficulty in realising research-induced efficiency gains in the developing tropics and suggest some of the underlying reasons for this. The paper articulates the difference between the influence and impact of research, and makes suggestions as to how research uptake processes can be better understood through the use of concepts such as ‘impact pathways’ and diffusion of innovations. The paper argues that researchers must go beyond passive dissemination of their outputs and invest in collaboration and alliances as important strategies to enhance research uptake and impact. The paper draws on previous studies of how science has influenced national and international forest related policy-debates, and on studies of the uptake of CIFOR's Criteria and Indicators research. The findings from these studies suggest that the lack of uptake and impact of most forestry research initiatives is due to a number of factors including: reliance on passive dissemination, poor understanding of research uptake and diffusion processes both at technical and policy levels and a lack of effective engagement or collaboration with influential actors. The paper argues that there should be a greater emphasis on 'action' research that includes 'policy actors' at various levels. Pragmatic strategies to enhance the likelihood of policy influence are described.